(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article examines modern approaches to sterility control in cosmetology clinics, as well as methods for monitoring and evaluating the effectiveness of sterilization procedures. It also highlights the historical development of asepsis and antisepsis principles, allowing us to trace the evolution of concepts of sterility and its importance in cosmetology practice. The main sources of microbial contamination, including personnel, instruments, air, and surfaces, are analyzed. The stages of instrument processing, including preliminary cleaning, disinfection, and sterilization, are described in detail, and the main sterilization methods, such as steam, air, and chemical, are discussed. Particular attention is paid to physicochemical and biological methods of sterility monitoring, including the use of indicators and spore-forming microorganisms. The paper also addresses issues related to monitoring system organization, documentation, and personnel training. It examines methods for monitoring air and surface microbial contamination, as well as approaches to assessing the effectiveness of sterilization processes. Current trends, including automated monitoring and the implementation of innovative technologies, are highlighted.